The Rise of Special Economic Zones in Bangladesh - World Bank (World Bank, Washington, DC, 2018)
The government recognizes that inadequate basic infrastructure and a severe shortage of accessible land discourages greenfield investments and industrial development.Bangladesh has one of the world’s most cost competitive, sizeable supply of labor, ideal for labor-intensive production in sectors such as garments, footwear, leather products and toys. However, despite large development success fueled by RMG, microfinance, and remittances, three out of five Bangladeshi workers still find themselves in vulnerable employment.The Bangladesh Export Processing Zones Authority Act of 1980 was aimed to boost industrialization and job creation through the promotion of trade and investment and it has had some success.The Act led to the establishment of the semi-autonomous Bangladesh Export Processing Zones Authority (BEPZA), which leases serviced land to industrial tenants in eight export processing zones (EPZs) across the country, primarily focused on the garment sector.The Bangladesh Economic Zones Authority Act and the Bangladesh Hi-Tech Park Authority Act—both of 2010—created two more agencies like BEPZA and these three agencies have overlapping mandates. The two new acts led to the creation of two new semi-autonomous agencies— the Bangladesh Economic Zones Authority (BEZA) and the Bangladesh Hi-Tech Park Authority (BHTPA)—tasked to oversee the expansion of economic zones (EZs) and hi-tech parks (HTPs) in the country.Bangladesh’s development agenda using special economic zones is affected by internal andexternal challenges that the government will need to address.These include: Legal and regulatory mandates, Governance and technical capacity, Safeguards management and Connections to the national investment climate.